I Workshop on Male Reproductive Biology - Kempinas, Wilma De Grava [UNESP]; Avellar, Maria Christina Werneck (Universidade Estadual Paulista (Unesp), 2008)
Proceedings of the I Workshop on Male Reproductive Biology carried out in Brazil, from November 05 to 07, 2007.